A closer look at accounting for Islamic financial institutions - Ismail, Nurazleena; Muhamad Sori, Zulkarnain (2017)
This paper provides a discussion of a study that examines accounting in Islamic perspectives. The discussion includes an overview of the development of Islamic finance, accounting in Islamic perspectives, and four key accounting assumptions, namely ‘substance over form’, ‘time value of money’, ‘fair value’ measurement and ‘recognition based on probability’, which serve as important guides to preparers of financial information.